2018
DOI: 10.1073/pnas.1718813115
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic switching enables efficient bacterial colonization in flow

Abstract: Bacteria colonize environments that contain networks of moving fluids, including digestive pathways, blood vasculature in animals, and the xylem and phloem networks in plants. In these flow networks, bacteria form distinct biofilm structures that have an important role in pathogenesis. The physical mechanisms that determine the spatial organization of bacteria in flow are not understood. Here, we show that the bacterium colonizes flow networks using a cyclical process that consists of surface attachment, upstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…An attractive feature of the BC is the possibility to create cellulose with a desired fibre structure at both macroscopic and nanoscopic scales in the process of the material formation, rather than using post-production treatment methods. Along with chemical and biological processes which affect the biofilm development, hydrodynamic flows in bacterial suspensions are also capable of shaping biofilms 14 . It has been recently demonstrated that when suspensions of E. coli are perturbed by surface waves, patterned biofilms at the liquid-solid interface are developed 15 .…”
Section: Introductionmentioning
confidence: 99%
“…An attractive feature of the BC is the possibility to create cellulose with a desired fibre structure at both macroscopic and nanoscopic scales in the process of the material formation, rather than using post-production treatment methods. Along with chemical and biological processes which affect the biofilm development, hydrodynamic flows in bacterial suspensions are also capable of shaping biofilms 14 . It has been recently demonstrated that when suspensions of E. coli are perturbed by surface waves, patterned biofilms at the liquid-solid interface are developed 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Biofouling and biocorrosion are ubiquitous, costly problems also in other settings, from industrial wastewater systems to marine environments 5,6 . To date, the mechanistic understanding of bacterial colonization of surfaces mainly focused on flat surfaces [7][8][9][10][11][12] ; yet in many applications surfaces are not flat. As a result, no general framework exists to account for the role of surface shape on bacterial colonization.…”
mentioning
confidence: 99%
“…Using a microfluidic device and P. aeruginosa as a model, cyclical events of attachment, detachment, and reattachment were observed, interspersed with periods of movement on the surface or within flow. This dynamic switching was proposed to maximize the spreading of the bacteria (45). Fluorescence lifetime imaging microscopy (FLIM) and spatial and temporal resolution with NADH as a metabolic marker revealed that surface attachment increases the levels of free NADH.…”
mentioning
confidence: 99%